Efficient small-sized implementation of the keyed-hash message authentication code - Yiakoumis, Ioannis; Michail, Harris; Papadonikolakis, Markos; Goutis, Costas E.; Kakarountas, Athanasios P. (My University, 2005)
A design approach to create small-sized high-speed implementations of the Keyed-Hash Message Authentication Code (HMAC) is presented. The proposed implementation can either operate in HMAC-MD5 and/or in HMAC-SHA1 mode, The proposed implementations do not introduce significant area penalty. However the achieved throughput presents an increase compared to commercially available IP cores that range from 30%-390%. The main contribution of the paper is the increase of the HMAC throughput to the required level to be used in modern telecommunication applications, such as VPN and the oncoming 802.11n. © 2005 IEEE.
Keywords: Hash function | High-speed HMAC | Message authentication | Security | VLSI implementation